2019
DOI: 10.1097/ajp.0000000000000742
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding Dexmedetomidine to Local Anesthetic Agents for Transversus Abdominis Plane Block

Abstract: Background: Dexmedetomidine (Dex) has been used as an adjuvant in transversus abdominis plane (TAP) blocks. This meta-analysis was aimed at evaluating the effect of Dex in TAP blocks. Objectives: Outcome measures were total opiate consumption in 24 hours after surgery, time to systemic rescue analgesia, pain scores after surgery, and adverse events (AEs). Materials and Methods: Randomized controlled trials c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Consistent with many previous studies, the hemodynamic adverse effects of dexmedetomidine reported in this study were mild and easily managed. 6,[22][23][24] Systemic absorption of the drug can influence patients' hemodynamics and analgesia and is important for optimum dosing strategies (interactions with other drugs).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with many previous studies, the hemodynamic adverse effects of dexmedetomidine reported in this study were mild and easily managed. 6,[22][23][24] Systemic absorption of the drug can influence patients' hemodynamics and analgesia and is important for optimum dosing strategies (interactions with other drugs).…”
Section: Discussionmentioning
confidence: 99%
“…41,43 Nevertheless, one recent meta-analysis showed no increase in the incidence of adverse effects. 44 This discrepancy might be due to differences in the routes of DEX absorption, type of surgery, or sample size among the meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, IND as monotherapy is not indicated for severely painful procedures, and its analgesic potential appears to be realized in conjunction with local anesthetics. 60 Future studies should explore the analgesic potential of IND for acutely painful procedures using rigorous methodology and optimal dosing.…”
Section: Discussionmentioning
confidence: 99%